Women, Text and the Canon: the Strange Case of 1 Corinthians 14:33-35 - Munro, Winsome 1925-1994 (1988)
Just when 1 Corinthians 14:33-35 could become the first passage in the Pauline collection to be assigned interpolation status by the common consent of Pauline scholars, certain feminist scholars have resisted this assignment as an apologetic strategem against the feminist critique of biblical religion. More recent developments either connect the passage with 1 Corinthians 11:2-16 as part of Pastoral-type editing, or read it as a citation of what Paul's opponents were saying to refute them. By contrast, in reconstructing the part of women in early Christian communities, Fiorenza assumes the Pauline origin of the material, arguing that Paul did not intend to limit the charismatic freedom of all women, but blaming him for introducing a patriarchalizing trend into the church. The present article prefers to recognize the full negative implications of the passage, and its close relation to the Pastoral epistles. If taken as an interpolation, its context in 1 Corinthians 14 emerges as a clue to the kind of egalitarian, charismatic community it opposes.